First detection of Sindbis virus in wild birds in Nigeria - Dickson Anoibi Matthew; Edvin Karlsson; Jonathan Ajik Izang; Linn Isberg; Jonas Näslund; Andreas Sjödin; Ulf Ottosson; Olivia Wesula Lwande; Jonas Waldenström (Scientific Reports)
Abstract Sindbis virus (SINV) is a zoonotic arbovirus transmitted by mosquitoes and maintained by wild birds with an expanding distribution globally. Despite its importance, surveillance efforts are low or lacking in many areas, especially in Africa. Our study aimed to highlight the epidemiology of SINV in wild birds in a West African country – Nigeria – with implications for human health. Blood samples were collected from wild resident Afrotropical and migrant Palearctic birds over two years. RT-qPCR was used to detect SINV RNA positive samples, followed by confirmatory conventional PCR and Sanger sequencing targeting the non-structural protein gene. Three out of 504 samples (0.6%; 95% CI: 0.12–1.73%) were positive for SINV, all from individuals of a single species, the African Thrush (Turdus pelios). We successfully generated the whole genome sequence of one sample. Phylogenetic analysis revealed it was closely related to strains from Algeria, Spain and Kenya in the SINV-I genotype. The study suggests that SINV is enzootic in the region and that the African Thrush may be a putative reservoir species.